Analisis Perbandingan Makna Balaghiyyah Antara Kamus Al-Ma’ani dan Google Gemini dalam Terjemahan Sya'ir Ibnu Rumi - Nailurrahmi, Fitma; Fauziyatullah, Hilma Auliya; Fuadah, Sulis Samrotul; Akmaliyah, Akmaliyah (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2025)
This study aims to analyze the comparative results of translating balaghiyyah meanings in Ibn al-Rumi elegiac poem using the traditional Al-Ma‘ani dictionary and Google Gemini. Employing a qualitative descriptive-comparative approach, the study uses six selected verses of Ibn al-Rumi poem and their translated outputs as the primary data. The findings reveal that the Al-Ma‘ani dictionary is superior in presenting deeper connotative meanings and the aesthetic values of classical Arabic, as it is grounded in lexical analysis and contextual semantics. Conversely, Google Gemini excels in efficiency and syntactic clarity but tends to produce literal translations that fail to capture the rhetorical and symbolic nuances. Thus, the study concludes that traditional dictionary-based translation remains more effective in preserving the balaghiyyah meaning of Arabic literary texts, while AI-based translation still requires further development to better comprehend figurative and expressive meanings.